THE EFFECTIVENESS OF PROCESS APPROACH IN TEACHING WRITING NARRATIVE TEXTS - Prisilya, Alma (2017)
This study explores the application of process approach in teaching writing. It examines (1) whether process approach affects the students' ability in writing narrative texts, and (2) the students' attitude toward the use of this approach. This study is both quantitative and qualitative. The data were collected from tests, students' portfolios, field notes, and questionnaires to eighth graders of a junior high school in Bandung. The results show that there is a significant difference in the students' ability in writing narrative texts after being taught by using process approach (p= .000, α= .05), indicating that process approach is effective for improving the students writing skill. It is also found that the students have shown some development in their writing skill and have developed positive values through the stages of the process approach. Finally, this study shows that the students have positive attitude toward the approach applied in this study. This study concludes that process approach is an effective approach for teaching narrative texts. ;--- Penelitian ini mengeksplor pengaplikasian pendekatan proses dalam pengajaran menulis. Penelitian ini membahas (1) apakah pendekatan proses mempengaruhi kemampuan siswa dalam menulis teks naratif, dan (2) sikap siswa terhadap pengaplikasian pendekatan mengajar ini. Penelitian ini menggunakan metode kualitatif dan kuantitatif (mix methods). Data penelitian diperoleh dari hasil tes, lembar kerja siswa, catatan lapangan, dan kuesioner yang didistribusikan pada siswa kelas delapan tingkat SMP di Bandung. Hasil penelitian menunjukan bahwa terdapat perbedaan yang sangat signifikan pada hasil menulis siswa setelah diajarkan menulis dengan menggunakan pendekatan proses (p= .000, α= .05), hal ini mengindikasikan bahwa pendekatan proses ini efektif untuk meningkatkan kemampuan menulis siswa. Dalam penelitian ini juga ditemukan bahwa para siswa menunjukan banyak perkembangan pada kemampuan menulis mereka serta mengembangkan nilai-nilai positif melalui setiap tahapan dalam pendekatan proses. Selain itu, para siswa juga menunjukan sikap positif terhadap pendekatan yang diterapkan. Kesimpulannya, pendekatan proses merupakan sebuah pendekatan yang efektif dalam mengajarkan menulis teks naratif.